2015
DOI: 10.5294/aqui.2015.15.2.6
|View full text |Cite
|
Sign up to set email alerts
|

La historia familiar y la conducta de consumo de alcohol como factor sociocultural en el adolescente. Perspectiva de enfermería

Abstract: Los adolescentes con mayor probabilidad de presentar la conducta de consumo de alcohol son los que están sometidos a diferentes factores de riesgo, los cuales pueden ser personales; dentro de estos factores se encuentra la historia familiar de consumo de alcohol (HFCA). Objetivo: establecer las diferencias y la relación entre el factor personal sociocultural a través de la HFCA y la conducta no saludable de consumo de alcohol en adolescentes de preparatoria del Estado de Nuevo León. Materiales y métodos: estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
2
0
6
Order By: Relevance
“…Armendáriz et al (2014), in a study of 680 university students in the state of Nuevo Leon, found that a family history of alcohol use influenced the students' own use (B = .080, p = .001). A subsequent study, with 240 high school students in the same state, found that greater alcohol use by parents was associated with an increased use by their children (rs = .196; p < .01) (Armendáriz et al, 2015). A study of 178 junior high school students in Campeche found a positive and significant relationship between family history of alcohol use and cumulative AUDIT score (rs = .164, p = .025), and also between that history and the number of alcoholic beverages the participants consumed (rs = .181, p = .005) (Telumbre et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Armendáriz et al (2014), in a study of 680 university students in the state of Nuevo Leon, found that a family history of alcohol use influenced the students' own use (B = .080, p = .001). A subsequent study, with 240 high school students in the same state, found that greater alcohol use by parents was associated with an increased use by their children (rs = .196; p < .01) (Armendáriz et al, 2015). A study of 178 junior high school students in Campeche found a positive and significant relationship between family history of alcohol use and cumulative AUDIT score (rs = .164, p = .025), and also between that history and the number of alcoholic beverages the participants consumed (rs = .181, p = .005) (Telumbre et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…The evidence for Mexico is also limited because the study populations have not been representative, and the majority of statistical analyses used have been univariate. Most international and Mexican studies have been based on non-probabilistic samples, which include only participants living in a particular region (Alati et al, 2014;Donovan & Molina, 2011;Haugland et al, 2013;Kovacs et al, 2008;MacLeod et al, 2008), who have a certain socioeconomic status (Capaldi et al, 2016;Casswell, Pledger, & Pratap, 2002), who live in areas with high crime rates (Bailey et al, 2006;Capaldi et al, 2016), or who are students from the same school (Armendáriz et al, 2015;Hernández, 2014). The nature of these samples limits the possible generalization of the results.…”
Section: Introductionmentioning
confidence: 99%
“…La teoría de la formación de expectativas hacia el alcohol, establece que las creencias del individuo acerca de esta conducta, se crean a partir del aprendizaje directo o vicario (Cassola, Pilatti, Aldarete, y Godoy, 2005). Así, los adolescentes cuyos familiares o grupo de iguales consumen alcohol, muestran en mayor medida esta conducta perjudicial (Armendáriz et al, 2015;Duffy, 2014;Pilatti, Godoy, y Brussino, 2011;Ruiz-Risueño, Ruiz-Ruiseño, y Zamarripa, 2012;Villareal, Sánchez-Sosa, Musitu, y Valera, 2010). Por tanto, sería adecuada la evaluación de estas variables a fin de conocer su relación con las expectativas del adolescente.…”
Section: Discussionunclassified
“…Para el presente proyecto de gestión del cuidado de Enfermería, se propone dividirlo en cuatro etapas, la primera es la "Detección de casos", en la que se buscan y detectan en coordinación con las autoridades educativas los adolescentes que sean hijos de padres consumidores de alcohol y que no hayan consumido alcohol alguna vez en su vida o se encuentren en el inicio de este; también es posible aplicar una cédula de datos personales y/o instrumentos, para identificar a los adolescentes que cumplan con esos criterios y que cuenten con un autoestima baja o media. Para evaluar la historia familiar de consumo de alcohol, existe el Inventario de Historia Familiar de Consumo de Alcohol, para detectar la presencia de consumo de los padres 7 . Para el consumo de alcohol actual, se encuentra el Cuestionario de Identificación de los Trastornos debidos al Consumo de Alcohol (AUDIT), para la identificación del consumo excesivo 24 .…”
Section: Figura 1 Adaptación De La Teoría De Autotrascendencia En Hiunclassified
“…Los hijos de padres alcohólicos son hasta cuatro veces más propensos a desarrollar problemas con la ingesta de alcohol 6 . Una investigación en Monterrey, México, encontró que los participantes con historia familiar, fueron quienes presentaron mayor consumo de alcohol 7 .…”
Section: Introductionunclassified